2016
DOI: 10.1007/s11046-016-0024-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Real-Time PCR and Platelia Galactomannan Assay for the Diagnosis of Invasive Pulmonary Aspergillosis: Bronchoalveolar Lavage Fluid Performs Better Than Serum in Non-neutropaenic Patients

Abstract: The diagnosis of invasive pulmonary aspergillosis (IPA) is still in challenge in clinical practice, particularly for those patients without an obvious neutropaenia. In this study, a well-validated qPCR method and Platelia galactomannan (GM) assay were compared for their diagnostic performance using paired samples of bronchoalveolar lavage (BAL) fluid and serum from predominantly non-neutropaenic patients. In the serum samples, qPCR showed a comparable performance with GM assay in terms of sensitivity and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The validity of other, non‐culture‐based methods for the detection of Aspergillus has gained traction over recent years, such that current proposals for the second revision of the EORTC/MSG definitions for IMI include consideration of Aspergillus PCR assays . PCR‐based assays have a wide range of reported sensitivities and have been suggested as a way to improve diagnostic accuracy when combined with other modalities, detect azole resistance and guide judicious use of preemptive antifungal treatment . Grancini et al suggested that BAL real‐time PCR, when performed in conjunction with routine BAL culture and GM, can have a NPV of 99% in immunocompromised patients, while Hoenigl et al reported 100% sensitivity and 98% specificity when combining PCR with GM.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of other, non‐culture‐based methods for the detection of Aspergillus has gained traction over recent years, such that current proposals for the second revision of the EORTC/MSG definitions for IMI include consideration of Aspergillus PCR assays . PCR‐based assays have a wide range of reported sensitivities and have been suggested as a way to improve diagnostic accuracy when combined with other modalities, detect azole resistance and guide judicious use of preemptive antifungal treatment . Grancini et al suggested that BAL real‐time PCR, when performed in conjunction with routine BAL culture and GM, can have a NPV of 99% in immunocompromised patients, while Hoenigl et al reported 100% sensitivity and 98% specificity when combining PCR with GM.…”
Section: Discussionmentioning
confidence: 99%
“…Two GM indexes !0.5 [16,30,31] and !1.0 [7,28,32] for BAL fluid have been proposed for the assessment of GM in diagnosis of IA due to A. fumigatus; however, to the best of our knowledge, data on A. flavus is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…There is as yet no consensus on how these tests could be used in the diagnostic strategy, and many issues arise, such as difficulties in the differentiation between infection and colonization [23]. A quantitative measurement of Aspergillus DNA could help on this regard, but this remains to be proved [25]. Aspergillus PCR is expected to be included in the next EORTC/MSG definitions of invasive fungal disease [22, 23].…”
Section: Casementioning
confidence: 99%